The Crucial Questions on Synovial Biopsy: When, Why, Who, What, Where, and How? - Ingegnoli, Francesca; Coletto, Lavinia Agra; Scotti, Isabella; Compagnoni, Riccardo; Randelli, Pietro Simone; Caporali, Roberto (Frontiers in Medicine, 2021)
Early changes in the organization of the synovial architecture are precocious and evident in the majority of joint diseases. Synovial tissue analysis might provide useful information for the diagnosis, especially in atypical and rare joint disorders, and might have a value in case of undifferentiated inflammatory arthritis, by improving disease classification. After a proper patient selection, it is crucial to address the dialogue between the clinician and the pathologist for adequately handling the sample, allowing the identification of histological patterns depending on the clinical suspicion. Moreover, synovial tissue analysis gives insight into disease progression helping patient stratification, by working as an actionable and mechanistic biomarker. Finally, it contributes to understanding joint disease pathogenesis, holding promise for identifying new synovial biomarkers and developing new therapeutic strategies. All of the indications mentioned above are not so far from being investigated in everyday clinical practice in tertiary referral hospitals thanks to the great feasibility and safety of old and more recent techniques such as ultrasound-guided needle biopsy and needle arthroscopy. Thus, even in rheumatology clinical practice pathobiology might be a key component in the management and treatment decision-making process. This review aims to examine some essential and crucial points regarding why, when, where, and how to perform a synovial biopsy in clinical practice and research settings and what information you might expect after a proper patient selection.